FAMILY NURSING CARE OF PHYSICAL MOBILITY DISORDERS IN PATIENT WITH POST STROKE IN BLULUK VILLAGE, LAMONGAN REGENCY - Iswatun, Iswatun; Endah sri Wijayanti; Rizkika Putri Silvia (Journal of Vocational Nursing, 2022)
Introduction: Stroke is brain damage due to blood supply to the brain, an event that suddenly takes place within 24 hours without realizing it, such as rupture of blood vessels in the brain and lack of blood supply in the brain. Prevalence by sex male 11.0% (10.5-11.5 per mile) 355,726 cases, female sex 10.9 (10.4-11.4 per mile) 358,056 cases. The proportion of stroke control to health care facilities in the population aged 15 years with stroke prevalence in East Java routinely 40.0% sometimes 39.5% not re-checking 20.5%. The purpose of this study was to carry out Family Nursing Care In Post Stroke Cases With Nursing Problems Of Physical Mobility Disorders. Methods: This research method uses a case study. Data were collected by means of interviews, observations, and documentation studies. Results: The results of the case studies indicate that there are gaps in the assessment of nursing care. Nursing diagnoses according to the IDHS lead to the main priority, namely Mobility Support (D.0045), priority nursing actions according to SIKI Mobilization Support (I.05173), with an outcome according to the SLKI Physical mobility (L.05042), evaluation of the main priority diagnoses, namely impaired mobility partially resolved by home visits for 6 days. Conclusions: Intervention combination Active and passive Range Of Movement techniques are very important for stroke patients. The family can motivate and teach the client to do this.